Interview with Bernardo Riego Amézaga - Sureda García, Bernat; Comas Rubí, Francisca (Historia y Memoria de la Educación, 2019)
Bernardo Riego Amézaga is a professor at the University of Cantabria. He has a PhD in Contemporary History. He has specialized in the history of images, a subject on which he has published reference books and scientific articles. His academic training, his beginnings as a researcher and teacher, his experience in the area of communication or his experience in politics, are information that appear in this interview, intertwined with his personal experiences and irremediably linked to issues on which Bernardo Riego reflects, and they range from methodological aspects related to the historical interpretation of images to current problems that affect research and university teaching.